A Novel Privacy and Copyright Protection Enforced Peer-to-Peer Network - Wang, Xiaoming; Zhu, Bin Benjamin; Li, Shipeng (Int. Conf. on Digital Rights Management: Technology, Issues, Challenges and Systems, 2005)
Peer-to-peer (P2P) networks are widely used to share copyrighted contents and software illegally around the world. Development and applications of P2P technologies have faced strong legal and legislative challenges. A P2P network has to have built-in copyright protection to enable P2P technologies to advance on its own without court’s and legislature’s interference. In this paper, we propose a novel and practical P2P network with a strong privacy protection and reliable tracking mechanism to track the original uploader of any material in the P2P network. When a pirated material is found, its uploader is tracked down, and can be punished by revoking the access to the network, removing his or her uploaded materials, etc. The whole protection system is completely transparent to end users. The proposed scheme would effectively deter users from uploading illegally any copyrighted materials to and dramatically reduce copyrighted materials shared through our P2P network.